The Influence of Leadership, Communication, Participation, and Local Community on The Development of Tourism Destinations in Mengesta Village - Yulianto, I Wayan Benyamin Eddy; Santoso, R. Tri Priyono Budi; Trimurti, Christimulia Purnama; Utama, I Gusti Bagus Rai (Eastasouth Institute, 2025)
This study aims to explain the influence of leadership, communication, participation, and local communities on the development of tourist destinations in Mengesta Village. This study uses a quantitative approach with an associative design. The population used is the entire community of Mengesta Village. The sample taken was 100 people from Mengesta Village using the probability sampling technique. The data collection method in this study was a questionnaire with a Likert scale. The analysis techniques used were descriptive analysis, multiple linear regression analysis, classical assumption test, determination analysis, F test, and t test. The results of this study indicate that 74.7% of the variation in tourist destination development in Mengesta Village is influenced by leadership, communication, participation, and local communities. Based on the hypothesis test, the results obtained were that leadership, communication, participation, and local communities have a positive and significant effect on the development of tourist destinations in Mengesta Village. Suggestions for further research are to develop further studies to identify factors that encourage the community to be involved in tourism development.